2019
DOI: 10.3390/info10100298
|View full text |Cite
|
Sign up to set email alerts
|

Subunits Inference and Lexicon Development Based on Pairwise Comparison of Utterances and Signs

Abstract: Communication languages convey information through the use of a set of symbols or units. Typically, this unit is word. When developing language technologies, as words in a language do not have the same prior probability, there may not be sufficient training data for each word to model. Furthermore, the training data may not cover all possible words in the language. Due to these data sparsity and word unit coverage issues, language technologies employ modeling of subword units or subunits, which are based on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The difficulty in using these methods is that it is not clear if the derived subunits are signerindependent and are language independent akin to phonemes in spoken language (which can be considered as speaker and language independent). More recently, a HMM-based approach was developed [15], where signer-independent hand movement subunits are derived based on light supervision. Through a preliminary crosslingual study it was demonstrated that the subunits derived could be shared across languages.…”
Section: Proposed Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…The difficulty in using these methods is that it is not clear if the derived subunits are signerindependent and are language independent akin to phonemes in spoken language (which can be considered as speaker and language independent). More recently, a HMM-based approach was developed [15], where signer-independent hand movement subunits are derived based on light supervision. Through a preliminary crosslingual study it was demonstrated that the subunits derived could be shared across languages.…”
Section: Proposed Approachmentioning
confidence: 99%
“…The hand movement subunits extraction was done according to the method presented in [15]. Briefly, the 3D skeleton position and velocity of both hands according to three different coordinate centers (head, shoulder and hip center) were used as feature observation (resulting a vector of size 36).…”
Section: Hand Movement Subunit Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hand movement subunits extraction was inspired by the method presented in [14]. Briefly, a 36 dimensional position and velocity features for both hands was extracted from the 3D skeleton with three different coordinate centers (head, shoulder and hip center).…”
Section: Hand Movement Subunits Posterior Probability Estimationmentioning
confidence: 99%